Clemastine Fumarate Protects Against Myocardial Ischemia Reperfusion Injury by Activating the TLR4/PI3K/Akt Signaling Pathway - Yuan, Xiaoxiao; Juan, Zhaodong; Zhang, Rui; Sun, Xiaotong; Yan, Ru; Yue, Feng; Huang, Yaru; Yu, Jiacheng; Xia, Xiaohui (Frontiers in Pharmacology, 2020)
Our pilot studies have shown that Clemastine Fumarate (CLE) can protect against myocardial ischemia-reperfusion injury (MIRI) through regulation of Toll like receptor 4 (TLR4). However, the protective mechanism of CLE and related signaling pathways for MIRI remains unclear. The objective of this study is to determine the mechanism by which CLE relieves MIRI in cardiomyocytes and its relationship with the TLR4/PI3K/Akt signaling pathway. CCK8 analysis was used to test the optimal concentration of TLR4 inhibitor CLI-095 and TLR4 agonist LPS on MIRI. The expression of inflammatory factors, oxidative stress response, cell damage, and intracellular calcium redistribution of cardiomyocytes were examined using the ELISA kits, Total Superoxide Dismutase Assay Kit with WST-8 and Lipid Peroxidation MDA Assay Kit, LDH Cytotoxicity Assay Kit, and laser scanning confocal microscope. The expression of TLR4/PI3K/Akt and cleaved caspase-3 were determined by Western blotting and immunofluorescent staining. Our results showed that MIRI aggravated the inflammatory response, oxidative stress, cellular damage of cardiomyocytes, and caused redistribution of intracellular calcium, upregulated the expression of TLR4 protein, cleaved caspase-3 protein, and down-regulated the expression of PI3K/Akt protein. After treatment with CLE, the inflammatory response, oxidative stress, and cellular damage of cardiomyocytes were alleviated, and intracellular calcium ion accumulation decreased. The expression of TLR4 protein, cleaved caspase-3 protein declined, but PI3K/Akt protein expression increased in cardiomyocytes treated with CLE. In addition, after treatment with the TLR4 inhibitor CLI-095, the results were similar to those of CLE treatment. The TLR4 agonist LPS aggravated the reactions caused by MIRI. The role of LPS was reversed after CLE treatment. These results suggested that CLE can attenuate MIRI by activating the TLR4/PI3K/Akt signaling pathway.